Inhibiting Fibronectin Attenuates Fibrosis and Improves Cardiac Function in a Model of Heart Failure. Issue 12 (18th September 2018) - Valiente-Alandi, Iñigo; Potter, Sarah J.; Salvador, Ane M.; Schafer, Allison E.; Schips, Tobias; Carrillo-Salinas, Francisco; Gibson, Aaron M.; Nieman, Michelle L.; Perkins, Charles; Sargent, Michelle A.; Huo, Jiuzhou; Lorenz, John N.; et al.
Abstract : Background: Fibronectin (FN) polymerization is necessary for collagen matrix deposition and is a key contributor to increased abundance of cardiac myofibroblasts (MFs) after cardiac injury. We hypothesized that interfering with FN polymerization or its genetic ablation in fibroblasts would attenuate MF and fibrosis and improve cardiac function after ischemia/reperfusion (I/R) injury. Methods: Mouse and human MFs were used to assess the impact of the FN polymerization inhibitor (pUR4) in attenuating pathological cellular features such as proliferation, migration, extracellular matrix deposition, and associated mechanisms. To evaluate the therapeutic potential of inhibiting FN polymerization in vivo, wild-type mice received daily intraperitoneal injections of either pUR4 or control peptide (III-11C) immediately after cardiac surgery for 7 consecutive days. Mice were analyzed 7 days after I/R to assess MF markers and inflammatory cell infiltration or 4 weeks after I/R to evaluate long-term effects of FN inhibition on cardiac function and fibrosis. Furthermore, inducible, fibroblast-restricted, FN gene–ablated (Tcf21 MerCreMer ; Fn flox ) mice were used to evaluate cell specificity of FN expression and polymerization in the heart. Results: pUR4 administration on activated MFs reduced FN and collagen deposition into the extracellular matrix and attenuated cell proliferation, likely mediated through decreased c-myc signaling. pUR4 also ameliorated fibroblast migration accompanied by increased β1 integrin internalization and reduced levels of phosphorylated focal adhesion kinase protein. In vivo, daily administration of pUR4 for 7 days after I/R significantly reduced MF markers and neutrophil infiltration. This treatment regimen also significantly attenuated myocardial dysfunction, pathological cardiac remodeling, and fibrosis up to 4 weeks after I/R. Last, inducible ablation of FN in fibroblasts after I/R resulted in significant functional cardioprotection with reduced hypertrophy and fibrosis. The addition of pUR4 to the FN-ablated mice did not confer further cardioprotection, suggesting that the salutary effects of inhibiting FN polymerization may be mediated largely through effects on FN secreted from the cardiac fibroblast lineage. Conclusions: Inhibiting FN polymerization or cardiac fibroblast gene expression attenuates pathological properties of MFs in vitro and ameliorates adverse cardiac remodeling and fibrosis in an in vivo model of heart failure. Interfering with FN polymerization may be a new therapeutic strategy for treating cardiac fibrosis and heart failure. Abstract : Supplemental Digital Content is available in the text.